The productivity, chemical composition and nutritional value of pastures dominated by Artemisia diffusa and Cousinia resinosa in arid lands of southwestern Uzbekistan - BAXRITDIN BAZAROV; ZAYNITDIN RAJAMURADOV; MARS SAFIN; ASATILLO RAJABOV; DAVRON KHAYITOV; MIRZOXID KUZIEV; SHARIFKUL AMINJONOV; MARKHAMAT ISMAYILOVA; JASUR KUDRATOV; MIRZAAHMAD KHUJABEKOV; DILOVAR KHAYDAROV (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bazarov B, Rajamuradov Z, Safin M, Rajabov A, Khayitov D, Kuziev M, Aminjonov S, Ismayilova M, Kudratov J, Khujabekov M, Khaydarov D. 2023. The productivity, chemical composition and nutritional value of pastures dominated by Artemisia diffusa and Cousinia resinosa in arid lands of southwestern Uzbekistan. Biodiversitas 24: 3916-3923. In recent years, extensive degradation of pastures has been observed all over the world as a result of drastic changes in climate and the increase of anthropogenic factors. As a result, the biological diversity of plant communities in pastures decreases, and specific changes occur in dry mass productivity, nutritional value, and other indicators of plant biomass. Therefore, studies aimed at assessing the condition of the vegetation in pastures are important. This research is one of the first studies of this type aimed at determining the biomass yield of pastures dominated by Artemisia diffusa Krasch. ex Poljako and Cousinia resinosa Juz. at varying elevations in arid areas of the southwestern regions of Uzbekistan, analyzing the chemical composition and nutritional value contained in the plants and evaluating the yield and quality of milk of goats fed with such plants. The results showed that dry mass yield, chemical composition, amount of substance, and nutritional value of the biomass produced by the plants in the pastures were directly influenced by the type of plants that make up the pasture, the elevation of the pastures, and climate factors (i.e., season). Our analysis also showed that the resiproductivity, chemical composition, and nutritional parameters were the highest in the mountain pastures compared to those in the hill and desert pastures. Goats fed by grazing in the pastures produced a higher yield and quality of milk compared to goats fed with conventional rations. The findings of this study explain the diversity of the productivity, chemical composition, nutritional value, and potential of the biomass produced by plants in pastures with dominant species A. diffusa and C. resinosa in increasing goat milk production in arid regions.